La normalisation comptable canadienne - Côté, Yves-Aubert (Assurances)

(untitled) (HEC Montréal, 1992)
This study on accounting standard setting in Canada, extracted from a paper on the Canadian accounting profession, was presented by the author at the University of Hosei in Tokyo in August 1992. lt is divided in three sections; historical development, existing accounting standard setting structure in Canada and prevailing orientations of Canadian accounting thought. The author concludes that Canadian accounting standard setting process is not beyond criticism. Yet, it undoubtedly reflects a thrust toward codifying practices, hence toward a greater coherence, a growing effort toward identifying solutions to emerging problems, a gradual assertion of a guiding role and a constant preoccupation to defend the role of professional judgment.